Light-Induced Polarization-Directed Growth of Optically Printed Gold Nanoparticles - Violi, Ianina Lucila (2016)
Optical printing has been proved a versatile and simple method to fabricate arbitrary arrays of colloidal nanoparticles (NPs) on substrates. Here, we show that is also a powerful tool for studying chemical reactions at the single NP level. We demonstrate that 60 nm gold NPs immobilized by optical printing can be used as seeds to obtain larger NPs by plasmon-assisted reduction of aqueous HAuCl4. The final size of each NP is simply controlled by the irradiation time. Moreover, we show conditions for which the growth occurs preferentially in the direction of light polarization, enabling the in situ anisotropic reshaping of the NPs in predetermined orientations.